Pengaruh Bullying terhadap Perkembangan Sosial-Emosional pada Anak Sekolah Dasar Negeri 14 Indralaya - Nabila Sultan Syakinah; Bella Fortuna; Alex Subrata (CV. Doki Course and Training, 2025)
Bullying is a serious problem in elementary schools that can hinder children's social and emotional development. This community service activity was carried out at Indralaya 14 Public Elementary School with the aim of increasing awareness and capacity of the school community in preventing and handling bullying behavior and minimizing its impact on students' social-emotional development. The implementation method included observations of the school environment, interviews and discussions with teachers, students, and parents, as well as mentoring in implementing empathy-based bullying prevention measures and strengthening teacher supervision. This activity involved four teachers, 15 students (victims, perpetrators, and witnesses), and five parents as partners. The results of the activity showed that bullying in schools occurs in verbal, physical, and social forms, resulting in anxiety, low self-confidence, and social withdrawal in the victim students. After mentoring and strengthening the prevention program, positive changes were seen in students, particularly increased courage to interact, participation in class activities, and learning motivation. This activity emphasized the importance of implementing a sustainable anti-bullying program through the integration of character education and collaboration between teachers, parents, and the school in creating a safe and conducive learning environment for children's development.